ANALISIS SIFAT MEKANIK KOMPOSIT SANDWICH SERAT KARBON TWILL 3K/DIVINYCELL FOAM DENGAN VARIASI METODE FABRIKASI - Kamila Nurul Aini; Arif Tjahjono; Nurul Lailatul Muzayadah; Afid Nugroho; Taufiq Satrio Nurtiasto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
Sandiwch composite is a type of structural composite material composed of a strong facesheet and a low-density core material. Sandwich composites have a high mechanical properties with their lightweight structure, so this material can be applied to aircraft structures. This study aims to determine the mechanical properties of carbon fiber sandwich composite twill 3K/divinycelll foam with various fabrication methods. The fabrication methods used vacuum bagging methods, and vacuum assisted resin infusion method. Mechanical tests conducted are flatwise compressive with ASTM C364 standard, edgewise compressive with ASTM C365 standard, flexural three point bending with ASTM C393 standard, and tensile strength with ASTM D3039 standard. In addition, scanning electron microscope test were also conducted to determine the morphology of the surface of the material and the bond between the fiber and the matrix. The results were obtained that vacuum asssisted resin infusion method has the most optimum mechanical with a high value in each test, such as the result of flexural three point bending of 47,51 MPa is better when compared with the result of vacuum bagging method of 18,70 MPa. Scanning electron microscope test results also showed that the vacuum assisted resin infusion method has the best morphology with perfect bond between matrix and fiber. So that it can be concluded that the most optimal mechanical properties of sandwich composites are produced by vacuum asssisted resin infusion method.